A Case Report of Renal Sympathetic Denervation for the Treatment of Polymorphic Ventricular Premature Complexes: Expanding Horizons - Kiuchi, Márcio Galindo (Medicine (Baltimore), 2015)
Premature ventricular complexes are very common, appearing most frequently in patients with hypertension, obesity, sleep apnea, and structural heart disease. Sympathetic hyperactivity plays a critical role in the development, maintenance, and aggravation of ventricular arrhythmias. Recently, Armaganijan et al reported the relevance of sympathetic activation in patients with ventricular arrhythmias and suggested a potential role for catheter-based renal sympathetic denervation in reducing the arrhythmic burden. In this report, we describe a 32-year-old hypertensive male patient presenting with a high incidence of polymorphic premature ventricular complexes on a 24 hour Holter monitor. Beginning 1 year prior, the patient experienced episodes of presyncope, syncope, and tachycardia palpitations. The patient was taking losartan 100 mg/day, which kept his blood pressure (BP) under control, and sotalol 160 mg twice daily. Bisoprolol 10 mg/day was used previously but was not successful for controlling the episodes. The 24 hour Holter performed after the onset of sotalol 160 mg twice daily showed a heart rate ranging between 48 (minimum)–78 (average)–119 (maximum) bpm; 14,286 polymorphic premature ventricular complexes; 3 episodes of nonsustained ventricular tachycardia, the largest composed of 4 beats at a rate of 197 bpm; and 14 isolated atrial ectopic beats. Cardiac magnetic resonance imaging with gadolinium perfusion performed at rest and under pharmacological stress with dipyridamole showed increased left atrial internal volume, preserved systolic global biventricular function, and an absence of infarcted or ischemic areas. The patient underwent bilateral renal sympathetic denervation. The only drug used postprocedure was losartan 25 mg/day. Three months after the patient underwent renal sympathetic denervation, the mean BP value dropped to 132/86 mmHg, the mean systolic/diastolic 24 hour ambulatory BP measurement was reduced to 128/83 mmHg, and the 24 hour Holter monitor showed a heart rate ranging between 51 (minimum)–67 (average)–108 (maximum) bpm, 854 polymorphic premature ventricular complexes, and no episodes of nonsustained ventricular tachycardia.